Legal writings on foreign investment in Vietnam (H. Ministry of planning and investment, 1998)
Contents: Investment law and implementing legal instruments; legal instruments on Tax and Finance; legal instruments on import, export and customs; legal instruments on banking - list of import substitutes; legal instruments on land, construction and tendering...
At head of title: Ministry of planning and investment
Keywords: Luật học